Предмет: Алгебра, автор: Афооня

Решите пожалуйста очень нужно. Номера 142 144 146

Приложения:

Ответы

Автор ответа: Жека3008
0
№142.
( frac{c}{b-c} - frac{c}{b} ): frac{c ^{2} }{b ^{2} } =(frac{bc}{b(b-c)} - frac{bc-c ^{2} }{b(b-c)} )* frac{b ^{2} }{c ^{2} } =frac{bc-bc+c ^{2} }{b(b-c)} *frac{b ^{2} }{c ^{2} }  = frac{ c^{2}  b^{2} }{b(b-c)*c ^{2} } = frac{b}{b-c}
№144.
( frac{a}{b}- frac{b}{a})* frac{b}{a-b}= frac{a ^{2}-b ^{2}  }{ab}* frac{b}{a-b}= frac{(a-b)(a+b)*b}{ab*(a-b)} = frac{a+b}{a}
№146.
 frac{c-3}{c} - frac{ c^{2} -9}{c}  *frac{1}{c-3}= frac{c-3}{c} - frac{ (c-3)(c+3)}{c}  *frac{1}{c-3}=frac{c-3}{c} - frac{ (c-3)(c+3)}{c*(c-3)} =frac{c-3}{c} - frac{ c+3}{c} =frac{c-3-c-3}{c}  =frac{-6}{c}
Похожие вопросы